Aplikasi Augmented Reality (AR) dengan Metode Marker Based sebagai Media Pengenalan Hewan Darat pada Anak Usia Dini menggunakan Algoritma Fast Corner Detection (FCD) - Adryan Syahputra; Septi Andryana; Aris Gunaryati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Education in children is not only learning from books, with the development of educational technology it can be done using technological equipment such as computers, smartphones, or gadgets. The use of the Augmented reality application can be used as an example in learning in early childhood by introducing land animals in 3D. This study aims to provide education, especially to children, about the introduction of land animals by utilizing augmented reality technology. This research uses a marker-based tracking method and a fast corner detection algorithm. The results of the study resulted in an application that contained the introduction of land animals consisting of dogs, horses, kangaroos, cats, wolves, elephants, deer, camels, giraffes, and cows. Brief information about each animal, designed to be as attractive as possible for children. Applications can run on the Android operating system.